LAJNAH TARBIYAH: INSTRUMEN PENGEMBANGAN NALAR KEAGAMAAN DAN KARAKTER RELIGIUS DI RAUDLATUL ULUM ARRAHMANIYAH SAMPANG - Mufarrahah Faishal; Imam Muslimin; Mulyono Mulyono (Kuttab : Jurnal Ilmu Pendidikan Islam, 2022)
The Raudlatul Ulum Arrahmaniyah Islamic Boarding School has an attractive education system known as Lajnah Tarbiyah Asasiyah, which is an education level devoted to new students to mature knowledge in the field of religion as well as to strengthen religious character. The purpose of this study is to reveal the extent of the contribution of Lajnah Tarbiyah in the development of Islamic scholarship and the character of students. The research succeeded in finding that the planning of the new santri intensive program was carried out through deliberation between the administrators and teachers at Lajnah Tarbiyah. The implementation of this program is realized through salaf schools, learning the basics of religion, especially in the field of fiqh, through studying the yellow book and learning to read and write Arabic. Meanwhile, the results of the intensive program are summarized in two aspects, namely the development of the potential for the religious field of new students and the development of the religious character of new students, such as istiqomah worship and accustomed to morality.